Tendências genéticas para características relacionadas à velocidade de crescimento em bovinos nelore na região nordeste do brasil - Malhado, Carlos Henrique Mendes [UNESP]; Filho, Raimundo Martins; Lôbo, Raimundo Nonato Braga; Facó, Olivardo; Azevedo, Danielle Maria Machado Ribeiro; De Souza, Julio César; Oliveira, Sonia Maria Pinheiro (FapUNIFESP (SciELO), 2005)
The objectives of this work were to estimate the genetic parameters and the genetic trends of the direct and maternal effects for the trait days to gain 160 kg (D160) in the pre-weaning period, and of the direct effect for the trait days to gain 240 kg (D240) in the post-weaning period, of animals of Nellore breed, born from 1965 to 2001 in the Northeast region of Brazil. The analyses were carried out using the MTDFREML software. For D160 the model included the direct and maternal genetic random effects and maternal permanent environmental effect, besides the fixed effects of contemporary group and the covariate age of dam at calving, assuming the covariance between maternal and direct effect equal to zero (σ am=0). For D240, the same fixed effects were considered, however, just the direct genetic effect as random. The genetic trends were estimated by linear regression of the breeding values on year of birth of the animals. The direct and maternal heritabilities for D160, respectively, were 0.12 ± 0.01 and 0.07 ± 0.02. The direct heritability for D240 was 0.16 ± 0.02. The genetic trends of the direct effects were significant, with estimated values of -0.14 and -0.41 days/year for D160 and D240, respectively. The genetic trend of the maternal effect for D160 was significant and equal to -0.0037 days/year. The genetic trends were favorable, however, inferiors the potential gain.
Genetic trends for traits related to the growth rate in nellore cattle raised in the northeast region of brazil
Keywords: Genetic gain; Genetic parameters; Heritabilities; Animalia; Bos taurus